2017
DOI: 10.21859/mej-103819
|View full text |Cite
|
Sign up to set email alerts
|

Moral Sensitivity and Moral Distress in Critical Care Unit Nurses

Abstract: Background and Aim: The present study was carried out aiming to determine the relationship between moral distress and moral sensitivity among nurses. Materials and Methods: This descriptive analytical study was conducted on 257 nurses employed in teaching hospitals affiliated to Birjand University of Medical Sciences (South Khorasan) in 2015. Available sampling was done among the nurses working in intensive care units (ICU, CCU, NICU and dialysis) in the whole province meeting the inclusion criteria. The data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 4 publications
4
21
1
1
Order By: Relevance
“…According to the correlational results, there was no significant relation between moral distress and caring behavior in emergency nurse (r=0/025). The results of the descriptive study named as "the correlation between moral distress and caring behavior of ICU nurse" stated that there was a significant, negative relation between moral distress and caring behavior (r=0/15), i.e., when nurses encounter increase in moral distress, they would have fewer caring behaviors (10), which was not consistent in its result with the present study; probably one of its reasons can be the significant relation between moral distress and the working unit (32), and the second reason can be the sampling type in that study in which individuals were included in the study through census, which forces a problem on generalization of results. While in our study, individuals were randomly selected.…”
Section: Discussioncontrasting
confidence: 86%
“…According to the correlational results, there was no significant relation between moral distress and caring behavior in emergency nurse (r=0/025). The results of the descriptive study named as "the correlation between moral distress and caring behavior of ICU nurse" stated that there was a significant, negative relation between moral distress and caring behavior (r=0/15), i.e., when nurses encounter increase in moral distress, they would have fewer caring behaviors (10), which was not consistent in its result with the present study; probably one of its reasons can be the significant relation between moral distress and the working unit (32), and the second reason can be the sampling type in that study in which individuals were included in the study through census, which forces a problem on generalization of results. While in our study, individuals were randomly selected.…”
Section: Discussioncontrasting
confidence: 86%
“…Lack of fulfillment of these objectives can lead to moral distress, which is in fact a common phenomenon in the nursing profession (3). As a huge group of caregivers, nurses are constantly faced with ethical issues that can play a significant role in their quality of care (5). Therefore, moral distress can have different effects on nurses, patients, and the health system and can result in significant consequences (6).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, moral distress can have different effects on nurses, patients, and the health system and can result in significant consequences (6). It has been shown in various studies that moral distress in a nurse can lead to job withdrawal, stress, burnout, job dissatisfaction, poor quality of work, incidence of physical symptoms such as headache and nightmare, reduced nursing confidence, and even prolonged patient hospitalization (5)(6)(7)(8). Several contributors to moral distress have been enumerated in studies conducted in different countries, including labor pressure, workforce shortage, working atmosphere, futile care, unnecessary tests on the patient, and incompetency of physicians and treatment team in fulfilling demands of patients and their families and making decisions for end-stage patients (7,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to our ndings, a number of studies have shown that formal employees had a higher level of awareness (38,44). Also, in the study of Mohammadi et al (2017), there was a signi cant relationship between ethics and \employment status. Ethical awareness was higher in people with contractual and formal employment status (1).…”
Section: Discussionmentioning
confidence: 93%
“…Moral sensitivity is an individual characteristic (23) and a basic need for nurses to recognize, interpret and answer ethical issues about the patient and to understand the potential impact of their actions on patients' health (24,25). Moral sensitivity is the core of moral literacy and is the most important and rst prerequisite for ethical practice in nursing care (26-31).…”
Section: Introductionmentioning
confidence: 99%